2007
DOI: 10.1074/jbc.m701050200
|View full text |Cite|
|
Sign up to set email alerts
|

The Human Angiotensin II Type 1 Receptor +1166 A/C Polymorphism Attenuates MicroRNA-155 Binding

Abstract: The adverse effects of angiotensin II (Ang II) are primarily mediated through the Ang II type 1 receptor (AT 1 R). A silent polymorphism (؉1166 A/C) in the human AT 1 R gene has been associated with cardiovascular disease, possibly as a result of enhanced AT 1 R activity. Because this polymorphism occurs in the 3-untranslated region of the human AT 1 R gene, the biological importance of this mutation has always been questionable. Computer alignment demonstrated that the ؉1166 A/C polymorphism occurred in a cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(178 citation statements)
references
References 48 publications
2
172
1
3
Order By: Relevance
“…The others did not influence canonical splicing sites, but they might theoretically influence perforin expression by disturbing exonic splicing enhancers, mRNA processing and transport, efficiency of codon usage by tRNA stability of mRNA secondary structure, protein folding or interaction with microRNA. [23][24][25][26][27][28] An alternative possibility is that they do not have a direct effect, but they are linkage disequilibrium with other unknown PRF1 mutations in the 5 0 UTR. However, we could not assess perforin expression because fresh cells from the carriers were not available.…”
Section: Discussionmentioning
confidence: 99%
“…The others did not influence canonical splicing sites, but they might theoretically influence perforin expression by disturbing exonic splicing enhancers, mRNA processing and transport, efficiency of codon usage by tRNA stability of mRNA secondary structure, protein folding or interaction with microRNA. [23][24][25][26][27][28] An alternative possibility is that they do not have a direct effect, but they are linkage disequilibrium with other unknown PRF1 mutations in the 5 0 UTR. However, we could not assess perforin expression because fresh cells from the carriers were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in miRNA target sites of protein-coding genes that are associated to cancer, [58][59][60] hypertension, 61 asthma, 62 cardiovascular disease 63 and polymorphisms in microRNAs that are associated with schizophrenia 40 were also described.…”
Section: Micrornas In Complex Diseasesmentioning
confidence: 99%
“…The authors suggest that allele-specific targeting of these miRNAs can account at least in part for the observations that HLA-G is associated with asthma. 62 In cardiovascular disease, Martin et al 63 reported an association of the human angiotensin II type 1 receptor polymorphism and miR-155. Finally, Hansen et al 40 identified important associations between brain-expressed miRNAs and schizophrenia for two SNPs located in mir-206 and mir-198 sequences.…”
Section: Micrornas In Complex Diseasesmentioning
confidence: 99%
“…Co-expression of target gene-miRNA pairs in affected tissue is shown for IP-VE genes. The numbers in parenthesis are the total number of genes/miRNA/ pairs for which expression data is available in the public domain Differential regulation of products of homologous alleles: polymorphism in miRNA target site SNP in the miRNA binding site can alter the interaction between the target site and miRNA, (73,74) and SNP in premiRNA can alter the biogenesis or the structure of the resulting mature miRNA (75) and, hence, the phenotype in question. When the source of miRNA is an intron, sequence polymorphism within the miRNA per se does not alter the mRNA of the source gene.…”
Section: Co-expression Of Mirna and The Target Genementioning
confidence: 99%